2010
DOI: 10.4049/jimmunol.1001713
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Vascular Endothelial Growth Factor Receptor-1– and Receptor-2–Mediated Signaling in T Cell Priming and Th17 Polarization to Lipopolysaccharide-Containing Allergens in the Lung

Abstract: Vascular endothelial growth factor (VEGF) is a key mediator in the development of airway immune dysfunction to inhaled allergens. However, the exact role of its receptors-mediated signaling is controversial. In this study, we evaluated the role of VEGF receptor (VEGFR)-1– and VEGFR-2–mediated signaling in T cell priming and polarization in the context of inhalation of LPS-containing allergens. A murine asthma model of mixed Th1 and Th17 cell responses was generated using intranasal sensitization with LPS-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…With respect to T cell polarization, polarizing cytokines, such as IL-12 and IL-6, released from DCs enhanced by VEGF are essential for the polarization of naive T cells into Th1 and Th17 cells, respectively (24,25). The present study showed that airway activation of FPRs downregulated Th1 and Th17 cell responses in the lung.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…With respect to T cell polarization, polarizing cytokines, such as IL-12 and IL-6, released from DCs enhanced by VEGF are essential for the polarization of naive T cells into Th1 and Th17 cells, respectively (24,25). The present study showed that airway activation of FPRs downregulated Th1 and Th17 cell responses in the lung.…”
Section: Discussionmentioning
confidence: 49%
“…Previous evidence showed that noneosinophilic inflammation induced by sensitization with LPS-containing allergens was caused by both Th1 and Th17 cell responses (6,24,25). To evaluate the effects of airway activation of FPRs on the development of Th1 and Th17 cell responses, W-peptide (200 mg/kg) was administered intranasally during sensitization, and immune responses were evaluated 6 h after the last allergen challenge (Fig.…”
Section: Effects Of Airway Activation Of Fprs On the Development Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…High dose LPS exposure specifically induces VEGF secretion by the airway epithelium. VEGF induces DC maturation and secretion of Th17 promoting cytokines like IL-6 ( Kim et al 2010). Up to 50% of asthma exacerbations are associated with viral infections (Grünberg et al 1997).…”
Section: Th17 Instructive Signals For DC Activation In Asthmamentioning
confidence: 99%
“…For example, the expression of several HIF-1 target genes is increased in the airway in asthma including vascular endothelial growth factor (VEGF) (11,12). In addition to promoting vascular remodeling and lymphangiogenesis, VEGF contributes to T-cell activation in response to inhaled allergens through distinct effects on dendritic and T cells (13,14). A nonbiased proteomic analysis revealed that several hypoxia-inducible, HIF-1-regulated proteins are upregulated in the lung in a mouse model of asthma, including several enzymes involved in glycolysis (15).…”
mentioning
confidence: 99%